Aligning with success: Adopting strategic alignment to improve decision effectiveness. Issue 1 (1st December 2020) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Strategic alignment can be used to boost decision effectiveness in organizations looking to gain a competitive advantage. Originality/value: The briefing saves busy executives, strategists and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.